Peningkatan Minat dan Aktivitas Belajar Biologi Siswa Kelas X1 SMA Negeri 1 Binamu Kabupaten Jeneponto Melalui Penerapan Model Pembelajaran Kooperatif Tipe Group Investigation - Asrianty Mas’ud (UNM Journal of Biological Education, 2018)
This study aims to: (1) improve students' interest in learning biology subject, and (2) improve the students' learning activity in biology subject at the ninth grade of SMA Negeri 1 Binamu in Jeneponto Regency, by applying the group investigation type of cooperative learning method. This is a Classroom Action Research conducted in two cycles which include: (a) Planning, (b) Action (treatment) , (c) Observation and Evaluation, and (d) Reflection. The results show that: (1) the students' interest in learning biology improves by 6,9% from cycle I to cycle II in the category of "very interested"; and (2) students' activity improved by 23,45% from cycle I to cycle II.